2019
DOI: 10.1111/nicc.12433
|View full text |Cite
|
Sign up to set email alerts
|

Light affects heart rate's 24‐h rhythmicity in intensive care unit patients: an observational study

Abstract: Background Intensive care unit (ICU) patients experience two affronts to normal 24‐h rhythms: largely internal events such as medication and external factors such as light, noise and nursing interventions. Aims and objectives We investigated the impact of light variance within an ICU on 24‐h rhythmicity of three key physiological parameters: heart rate (HR), mean arterial blood pressure (MAP) and body temperature (BT) in this patient population. Design Patients were assigned to beds either in the ‘light’ or ‘d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“…We found that ACTG maybe useful to record and distinguish the rest-activity circadian rhythms in ICU patients. According to our preliminary data, our ICU light exposure (lux) during daytime and nighttime are within the normal range [7]. Also, M-10 and L-5 measurements in our population are higher, RA is lower and IS, is higher compared to healthy population [3,4].…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…We found that ACTG maybe useful to record and distinguish the rest-activity circadian rhythms in ICU patients. According to our preliminary data, our ICU light exposure (lux) during daytime and nighttime are within the normal range [7]. Also, M-10 and L-5 measurements in our population are higher, RA is lower and IS, is higher compared to healthy population [3,4].…”
Section: Discussionsupporting
confidence: 56%
“…This observational study was conducted in a small, single-ward University ICU at a Greek general hospital in Athens, as refereed to a previous study [7]. Generally, total admissions to this ICU are low because the study site is a training hospital without a highdependency unit (HDU), with HDU patients instead assigned to the ICU, resulting in a long mean length of stay.…”
Section: Methodsmentioning
confidence: 99%
“…Poor environments in ICUs can be potentially inimical for the critically ill patients 23 . Inappropriate lighting has been shown to cause incidents and increased heart rates, indicating the patients are under stress 24,25 . Noise is often still found to be well above the WHO recommendations, resulting in disturbed circadian rhythm and causing delirium in intensive care patients 26,27 .…”
Section: Introductionmentioning
confidence: 99%
“…Alterations to melatonin levels are observed in critically ill patients at the intensive care unit (ICU) [8]. Plenty of factors, such as light, noise and interventions pertinent to the ICU environment, have been demonstrated to worsen variability to the 24-h rhythms of many body functions [9]. The 24-h variability of physiological parameters such as heart rate, mean arterial pressure and body temperature are affected [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Plenty of factors, such as light, noise and interventions pertinent to the ICU environment, have been demonstrated to worsen variability to the 24-h rhythms of many body functions [9]. The 24-h variability of physiological parameters such as heart rate, mean arterial pressure and body temperature are affected [9][10][11]. Furthermore, the critical illness per se and sepsis, which is a clinical state during the stay in the ICU, can lead to circadian dysrhythmia and melatonin variability disturbance, as many studies have demonstrated [12].…”
Section: Introductionmentioning
confidence: 99%